Top-down modulation of the perception of other people in schizophrenia and autism - Cook, Jennifer L.; Barbalat, Guillaume; Blakemore, Sarah-Jayne (Frontiers in Human Neuroscience, 2012)
Accurately and efficiently perceiving social cues such as body movements and facial expressions is important in social interaction. Accurate social perception of this kind does not solely rely on ‘bottom-up’ visual processing but is also subject to modulation by ‘top-down’ signals. For example, if instructed to look for signs of happiness rather than fear, participants are more likely to categorise facial expressions as happy – this prior expectation biases subsequent perception. Top down modulation is also important in our reactions to others. For example, top down control over imitation plays an important role in the development of smooth and harmonious social interactions. This paper highlights the importance of top-down modulation in our perception of, and reactions to, others. We discuss evidence that top-down modulation of social perception and imitation is atypical in Autism Spectrum Conditions and in schizophrenia, and we consider the effect this may have on the development of social interactions for individuals with these developmental disorders.